Biological indicators of animal welfare in rodents in the biological essay laboratory of the University of Costa Rica: Evaluation protocols - Herrera Ruiz, Carolina (2019)
Animal welfare can be affected by many factors that compromise both physical and mental health, that is why the more objective relationships are provided, the greater the likelihood of identifying the state of well-being of the animals. The purpose of this paper was to provide a rapid assessment protocol for biological indicators of animal welfare. The protocol was validated by two workers from the bioterium of the Biological Essay Laboratory of the University of Costa Rica by applying it in two animal colonies: female and male HSD:SD rats, and female and male HSD: IC mice. The evaluators reported two types of affections such as the presence of hematoporphyrin in rats and the presence of alopecia in mice. In both colonies, these results showed that there are no differences with the proposed tool.